Realización del cortometraje de género musical “una primera cita” - Balbuena Chincha, André Israel (2020)
This project consists of a fiction short film of approximately 13 minutes, which belongs to the musical genre, written and directed by André Balbuena and produced by Maria Fernanda Mendoza. This project seeks to expand the offer of musical cinema in Peru. Despite recent productions that try to rescue the musical, it is a genre little explored in national production. The short film includes an original song that contributes to the development and advancement of the story and that involves the characters in a dream world with respect to the verisimilitude of the rest of the story. This audiovisual proposal contains nuances of the romantic comedy since the story is about the intense search for love. Filming took place on October 13 and 14, 2018 in Lima, Peru and post-production culminated in August 2019. The short film has been screened at 4 film festivals in Peru and in 3 alternative theaters. It was also the recipient of the Best Sound award in the framework of the II Valor 2019 Latin American Short Film Festival.